Size effects in a silica-polystyrene nanocomposite: Molecular dynamics and surface-enhanced continuum approaches - Davydov, Denis; Voyiatzis, E; Chatzigeorgiou, Georgios; Liu, S; Steinmann, Paul; Böhm, M; Müller-Plathe, F. (Soft Materials, 2014)
Size effects in a system composed of a polymer matrix with a single silica nanoparticle are studied using molecular dynamics and surface-enhanced continuum approaches. The dependence of the composites mechanical properties on the nanoparticles radius was examined. Mean values of the elastic moduli obtained using molecular dynamics were found to be lower than those of the polystyrene matrix alone. The surface-enhanced continuum theory produced a satisfactory fit of macroscopic stresses developing during relaxation due to the interface tension and uniaxial deformation. Neither analytical nor finite-element solutions correlated well with the size-effect in elastic moduli predicted by the molecular dynamics simulations.
Keywords: Molecular dynamics; Nanocomposite; Size effect; Surface energy; Surface-enhanced continuum